The fingerprint nature of PCDD in iron ore sinter strand emissions, the effect of suppressants and alternative fuels, and the potential for comparison with the isomer profile of PCDF. (January 2018) - Ooi, Tze C.; Thompson, Dennis; Anderson, David R.; Fisher, Ray
Abstract: It has been previously shown that the isomer profile of PCDF emissions from iron ore sinter plant only varies within limits even when suppressants or alternative fuels are added, to the extent that it can be said to have a 'fingerprint'. The isomer profiles of PCDD from tetra- to hexacholrodibenzo-p-dioxin from the same samples examined for PCDF emissions have been obtained, and show the same tendency for a 'fingerprint ' isomer distribution to occur. Occasional exceptionally high isomer abundances are observed, but these are uncommon. The potential for comparison of the abundances of PCDF and PCDD isomers with similar chlorination patterns to determine whether the same formation process is involved has been examined. It is found that co-elutions prevent extensive comparisons irrespective of whether the SP2331 or DB5ms column is used in the analyses for separation of isomers to provide the results used for comparisons, although they allow limited results to be obtained. It is suggested that analyses using the two chromatography columns to analyse the same sample in parallel could provide more resolution of the isomer profiles for use in comparisons. A pilot study using samples analysed using each column is limited because of detailed differences in the emissions profiles, but demonstrates that greater resolution is possible if the two columns are used to analyse one sample. Highlights: Unique isomer distribution profiles along two sinter strands are presented. The profiles are similar at each windleg and are similar to those form sinter pot trials. Suppressants and alternative fuels do not alter the pot trial profiles. Only limited comparison with PCDF profiles is possible because of co-elutions. Analysis with two columns in parallel can reduce multi-isomer abundance estimation.